DEVELOPMENT OF THEMATIC TEACHING MATERIALS BASED ON LOCAL WISDOM IN GRADE IV ELEMENTARY SCHOOL OF NORTH ACEH REGENCY - Sitti 'Abidah; Daulat Saragi; Reh Bungana Beru Perangin-angin (Jurnal Ilmiah Teunuleh, 2021)
In general, teaching materials and learning processes tend to be teacher-centered, while students only listen to what is conveyed by the teacher. So that the teaching materials used have less impact on improving student learning outcomes. From that tendency, researchers took the basis of research on students of Grade V Elementary School in North Aceh Regency with the aim to produce thematic teaching materials products based on local wisdom that are in accordance with the demands of KD / KI in the 2013 curriculum, further to find out the practicality of local wisdom-based thematic teaching materials that have been developed; and to find out the effectiveness of thematic teaching materials based on local wisdom that has been developed. Based on individual completion criteria, it can be determined that students who have completed their individual studies are known that classical completion has reached 88.00%. So that the results of learning classically are complete. In other words, it can be stated that student learning outcomes taught with thematic teaching materials based on local wisdom are higher than the learning outcomes of students taught with learning models that have been used by teachers.